Identification of Commercial Oxo-Biodegradable Plastics: Study of UV Induced Degradation in an Effort to Combat Plastic Waste Accumulation - Antelava, Ana; Konstantinou, Achilleas; Bumajdad, Ali; Manos, George; Dewil, Raf; Al-Salem, Sultan Majed (My University, 2020)
Abstract: End of life single-use items such as carrier bags constitute a large proportion of the litter found in marine and terrestrial environments. The main objective of the current work was to investigate the response of an oxo-biodegradable commercial plastic film product to photo-degradation using accelerated weathering, verifying the claim of its biodegradability and suitability as an eco-friendly product. This study is also geared towards the appropriateness of such products to reduce plastic waste accumulation in urban environments. The film samples were exposed to weathering as a means to determine the impact of UV induced oxo-biodegradation. Haze (%), light transmission (%) and the total change in colour (ΔE) were measured as indicators to the degradation profile of the polymeric materials, in addition to tensile pull mechanical properties and thermal stability. The melting peak indicates the melting point (Tm) of the polymer and with exposure to weathering it showed a slight decrease from 105 to 102 °C indicating that biodegradation mechanisms were triggered to a certain extent. The reduction in strain at rupture was also indicative for a loss in crystalline structure, coupled with Young’s modulus increase throughout the weathering exposure tests. Therefore, the material studied could be a candidate to mitigate the accumulation of plastic waste in open environments based on the results of this study whilst regulating controlled substances.
Keywords: Colour; Haze; Oxo-biodegradable; Plastic film; TGA